2021
DOI: 10.1159/000512867
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Differences between Liquid-Based Cytology and Conventional Preparation in Endometrial Endometrioid Carcinoma Grade 1 and Grade 3, and the Differentiation of Grades in Each Method

Abstract: Introduction: Direct smearing preparation (conventional preparation [CP]) has been widely used for endometrial cytology in Japan. In CP, sampling and screening errors are problematic. In liquid-based cytology preparation (LBC), the problems of CP can be solved. But there is a problem that cytological findings of LBC are different from those of CP. The purpose of this study was to evaluate the differences of morphological findings of endometrial cytology between LBC and CP, and the usefulness of the endometrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 16 publications
3
4
1
Order By: Relevance
“…The roundness of cluster was G1>G3 and G1>Serous, and the complexity of cluster was G1<G3 and G1<Serous, both showing significant differences. By image analysis of endometrial LBC (SurePath) specimens collected with Softcyte, although the differences were not significant between the grades of EC, a tendency similar to the results of our present study was observed [20]. The roundness was higher in G1 than in G3, and the complexity was higher in G3 than in G1, probably reflecting that G1 consists of rounder papillary clusters and that G3 consists of more complex clusters, which are loosened due to weakened cell binding.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The roundness of cluster was G1>G3 and G1>Serous, and the complexity of cluster was G1<G3 and G1<Serous, both showing significant differences. By image analysis of endometrial LBC (SurePath) specimens collected with Softcyte, although the differences were not significant between the grades of EC, a tendency similar to the results of our present study was observed [20]. The roundness was higher in G1 than in G3, and the complexity was higher in G3 than in G1, probably reflecting that G1 consists of rounder papillary clusters and that G3 consists of more complex clusters, which are loosened due to weakened cell binding.…”
Section: Discussionsupporting
confidence: 89%
“…There is a report that the N/N ratio between G1 and G3 was G1<G3. In this report, the N/N ratio was G1 (0.056 ± 0.002)<G3 (0.068 ± 0.002), because the area of nucleus was nearly the same between G1 and G3 due to the marked nuclear shrinkage in G3 while the size of nucleolus was G1<G3 [20]. The N/N ratio between G3 and Serous was G3<Serous because the nucleus enlargement rate of Serous relative to G3 was 1.30 (70.9/54.6), but the nucleolus enlargement rate was higher at 1.43 (4.70/3.27).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations